2021
DOI: 10.1186/s13075-021-02424-y
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of survivin in children with oligo- and polyarticular juvenile idiopathic arthritis (JIA): diagnostic and prognostic value—a single-center study

Abstract: Aim The goal of the study was to assess the diagnostic and prognostic utility of survivin in patients with juvenile idiopathic arthritis (JIA). Methods Seventy children with JIA—59 newly diagnosed and 11 biologically treated (46 girls and 17 boys) aged 1.5–18 years and 29 healthy children as a control group, appropriately matched in terms of sex and age, were included in the study. The disease activity was established on the basis of the JADAS-27 c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…A relevant study conducted on 70 JIA patients and 29 age and sex matched controls reported higher serum survivin expression in children with JIA compared to the control group. 18 Survivin over-expression was significantly associated with a polyarticular onset in the active phase of the disease. It was found useful in detecting patients with unfavorable prognosis who need extensive pharmacological therapy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A relevant study conducted on 70 JIA patients and 29 age and sex matched controls reported higher serum survivin expression in children with JIA compared to the control group. 18 Survivin over-expression was significantly associated with a polyarticular onset in the active phase of the disease. It was found useful in detecting patients with unfavorable prognosis who need extensive pharmacological therapy.…”
Section: Discussionmentioning
confidence: 97%
“…In all synovial fluid samples, the concentration of survivin was higher than its matched level in the serum (p = 0.003). 18 On the contrary, a study on 123 adult rheumatoid arthritis patients revealed that survivin plasma levels were detectable in only 13.8% of patients. Survivin positivity did not correlate with RF (p = 0.180) or anti-CCP antibody levels (p = 0.926).…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we tested survivin as a potential biomarker of disease activity and treatment response. Increased expression of survivin was previously demonstrated in several autoimmune diseases like rheumatoid arthritis, juvenile idiopathic arthritis, myasthenia gravis, multiple sclerosis, psoriasis, systemic sclerosis, 25,[33][34][35][36][37][38] and its regulation has served as a marker of immune cells apoptosis inhibition and response to treatment. 23,25,37,39 Although oestrogen regulates various facet of autoimmune diseases, the aspects of oestrogen-mediated effects on survivin are not clarified in each of them as they are in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A expressão aumentada de survivina já foi demonstrada em muitas doenças autoimunes como artrite reumatoide, artrite idiopática juvenil, miastenia gravis, esclerose múltipla, psoríase e esclerose sistêmica (Bokarewa, Brink, Erlandsson, & Dahlqvist, 2014;Galeotti et al, 2008;Gravina et al, 2017;Lipinska, Kaszkowiak, Malachowska, Swidrowska-Jaros, & Smolewska, 2021;Sharief, Noori, Douglas, & Semra, 2002;Wang, Zhang, Xia, Zhang, & Zhang, 2016;Zafari et al, 2019) e essa regulação tem sido utilizada como marcador de inibição da apoptose de células imunes e resposta para o tratamento (Ebrahimiyan et al, 2018;Gravina et al, 2017;Mokuda et al, 2015;Zafari et al, 2019).…”
Section: Discussionunclassified